The Etiquette of Social Interaction within the Household in Surah An-Nur Verses 58-61: An Analysis based on Tafsir Ibn Kathir's - Iqbal, Achmad Ichsanul Alaudin (Universitas Muhammadiyah Surakarta, 2023)
As Muslims, implementing the verses of the Quran as a guide for life is essential. The Quran specifically addresses good morals and etiquette when visiting the homes of others. This is particularly crucial as, in the present time, many people lack an understanding of proper visiting etiquette. Surah An-Nur verses 58-61 provide guidance on manners and ethics in social interactions and within the family in Islamic teachings. These verses emphasize the importance of proper conduct when entering a house, dressing modestly, and maintaining privacy in social interactions. This research aims to analyze the ethical values contained in the interpretation of Surah An-Nur verses 58-61 regarding family interactions according to various scholars and commentators. The study involves the analysis of classical and contemporary commentaries explaining these verses. Various commentaries such as Ibn Kathir, al-Razi, al-Jalalain, and others are utilized to comprehend the context, meaning, and practical application of the ethical values within these verses. Verse 58 underscores the etiquette of entering a house, emphasizing the respect for privacy. Verse 59 discusses the importance of dressing modestly to preserve purity and self-respect. Verses 60 and 61 highlight prohibitions against invading privacy, emphasizing that these rules are guidance from Allah to regulate human interactions with dignity. This research depicts the importance of ethics in family interactions, highlighting the values contained in Surah An-Nur verses 58-61, and their relevance in the context of social and familial life.